1983
DOI: 10.1017/s0021859600033463
|View full text |Cite
|
Sign up to set email alerts
|

Body heat storage in steers (Bos taurus) in fluctuating thermal environments

Abstract: Heat stored in the body of cattle subjected to a daily 10 C C range of environmental temperature was measured by calorimetry and thermometry. The daily range of bodycore temperature of the animals was of the order of 0-5 °C but mean skin temperature cycled with a range of approximately 6 °C. Calorimetric estimates of changes in mean body temperature showed good agreement with thermometric estimates when core and mean body temperature changes were weighted in the ratio a: (1 -a) where a was found to be 0-85. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…However, under too high environmental temperatures the thermal equilibrium can hardly be attained and in these circumstances the heat excess can be stored in the body tissues (Finch, 1985;McLean et al, 1983), thus increasing body temperature.…”
Section: Introductionmentioning
confidence: 99%
“…However, under too high environmental temperatures the thermal equilibrium can hardly be attained and in these circumstances the heat excess can be stored in the body tissues (Finch, 1985;McLean et al, 1983), thus increasing body temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Silva & Starling (2003) estimaram média de 48,14 W/m 2 para evaporação na superfície corporal e de 27,24 W/m 2 para evaporação respiratória em ovinos da raça Corriedale do mesmo rebanho submetidos às condições de temperaturas do ar similares às utilizadas neste trabalho. O fluxo de calor latente de aproximadamente 75,38 W/m 2 estimado por esses autores parece não ser suficiente para a manutenção da temperatura corporal estável (Figuras 1 e 3) nesses animais, uma vez que ocorreu elevação da temperatura retal quando a temperatura do ar foi superior a 40 o C, certamente em razão da estocagem de energia térmica (McLean et al, 1983).…”
Section: Resultsunclassified
“…To provide a satisfactory method of estimating changes in heat storage, McLean et al (1983b) found that the high temperatures noted on all skin regions (lower trunk, upper limb, lower limb and ear) suggest that the skin of the animals was fully vasodilated when the ambient temperature was high. When the ambient temperature fell; however, the effects of vasoconstriction were apparent with successively lower temperatures recorded on the skin regions.…”
Section: Skin Temperaturementioning
confidence: 99%
“…When an animal lies down both lower limb and dewlap temperatures can be affected by contact with the floor, the metalwork of the holding stall or with other skin regions and it becomes difficult to distinguish between the effects of postural and thermal influences on these temperatures (McLean et al 1983b).…”
Section: Skin Temperaturementioning
confidence: 99%
See 1 more Smart Citation